The Effect of Digital Literacy on Students’ Self-Disclosure in Online Counseling Sessions - Ledyva Yolanda; Ari Prasetyoaji (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2026)
Study aims to empirically examine the influence of digital literacy on the self-disclosure of Generation Z college students during online counseling sessions. Using a quantitative approach with a causal associative method, data were collected from 2,134 active students in Indonesia. The findings indicate that digital literacy has a significant positive impact on self-disclosure. Although students exhibit exceptionally high technical digital skills, a critical gap exists in digital safety literacy, which triggers a "privacy paradox" and self-censorship behaviors. Students feel more secure and open during text-based sessions (chat) compared to video calls, which are perceived as more intimidating. Furthermore, the study reveals significant gender differences, where male students demonstrate lower self-disclosure due to masculinity constructs and cultural barriers like ewuh pakewuh. These results suggest that the effectiveness of online counseling depends not only on advanced applications but also on strengthening students' digital security literacy. Integrating digital privacy education is essential to mitigate psychological barriers and foster a secure therapeutic environment.